BOOSTING THE TEACHING MOTIVATION FOR INTERNATIONAL LECTURERS THROUGH THE MASTERING OF THE CLASSROOM ENGLISH PHRASES - jaenal, jaenal (TEXTURA, 2021)
The title of the research aims to know the role of the classroom English phrases for international lecturers. Even though they do not teach English, they have to practice some English phrases, like instructions. In this research, the writer used a descriptive method through literature study by collecting some data taken from relevant books or websites. The result of research shows that classroom English phrases are really required for the international lecturers. The lecturers are strongly obliged to memorize some important phrases. As a result, they have to practice them in front of the students.Last but not least, the writer suggests that the international lecturers should learn hard about the English classroom phrases. Therefore, they will feel more confident when they have to face the students. Indirectly, that they can boost their motivation when they teach.